(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The objective of the research is to determine the correlation and influence relationship between the independent variable neuromarketing with its dimensions represented by (product, pricing, distribution, promotion) and the dependent variable consumer behavior with its dimensions represented by (environmental awareness, consumer perception of the product, consumer education level, consumer economic condition, benefits perception, social influence) and the degree of arranging these dimensions according to priority.